Effect of post-polymerization heat treatments on the cytotoxicity of two denture base acrylic resins Efeito de tratamentos térmicos após a polimerização sobre a citotoxicidade de duas resinas acrílicas para base de próteses - Janaina Habib Jorge; Eunice Teresinha Giampaolo; Carlos Eduardo Vergani; Ana Lúcia Machado; Ana Cláudia Pavarina; Iracilda Zeppone Carlos (University of São Paulo, 2006)
INTRODUCTION: Most denture base acrylic resins have polymethylmethacrylate in their composition. Several authors have discussed the polymerization process involved in converting monomer into polymer because adequate polymerization is a crucial factor in optimizing the physical properties and biocompatibility of denture base acrylic resins. To ensure the safety of these materials, in vitro cytotoxicity assays have been developed as preliminary screening tests to evaluate material biocompatibility. ³H-thymidine incorporation test, which measures the number of cells synthesizing DNA, is one of the biological assays suggested for cytotoxicity testing. AIM: The purpose of this study was to investigate, using ³H-thymidine incorporation test, the effect of microwave and water-bath post-polymerization heat treatments on the cytotoxicity of two denture base acrylic resins. MATERIALS AND METHODS: Nine disc-shaped specimens (10 x 1 mm) of each denture base resin (Lucitone 550 and QC 20) were prepared according to the manufacturers' recommendations and stored in distilled water at 37ºC for 48 h. The specimens were assigned to 3 groups: 1) post-polymerization in a microwave oven for 3 min at 500 W; 2) post-polymerization in water-bath at 55º C for 60 min; and 3) without post-polymerization. For preparation of eluates, 3 discs were placed into a sterile glass vial with 9 mL of Eagle's medium and incubated at 37ºC for 24 h. The cytotoxic effect of the eluates was evaluated by ³H-thymidine incorporation. RESULTS: The results showed that the components leached from the resins were cytotoxic to L929 cells, except for the specimens heat treated in water bath (p<0.05). Compared to the group with no heat treatment, water-bath decreased the cytotoxicity of the denture base acrylic resins. CONCLUSION: The in vitro cytotoxicity of the tested denture base materials was not influenced by microwave post-polymerization heat treatment. INTRODUÇÃO: A maioria das resinas acrílicas utilizadas para confecção de bases de próteses é composta pelo polimetacilato de metila. Muitos autores têm discutido o processo de polimerização dessas resinas em relação à conversão do monômero em polímero devido a sua importância na melhora da biocompatibilidade e das propriedades físicas. Para assegurar a utilização desses materiais, testes preliminares de citotoxicidade in vitro têm sido desenvolvidos para avaliação da biocompatibilidade. Um dos ensaios biológicos sugeridos para a análise da citotoxicidade é o teste de incorporação de ³H-timidina, o qual mede o número de células por meio da síntese de DNA. OBJETIVO: O objetivo do presente estudo foi avaliar, por meio do teste de incorporação de ³H-timidina, a citotoxicidade de duas resinas acrílicas para base de próteses submetidas aos tratamentos em microondas e em banho de água após a polimerização. MATERIAL E MÉTODO: Nove corpos-de-prova em forma de discos (10 x 1 mm) foram confeccionados com as resinas acrílicas Lucitone 550 e QC 20 de acordo com as instruções dos fabricantes, e foram armazenados em água destilada a 37ºC por 48 h. Os corpos-de-prova foram divididos em três grupos: 1) tratamento em forno de microondas por 3 min a 500 W; 2) tratamento em banho de água a 55ºC por 60 min; e 3) sem tratamento térmico. Extratos foram preparados pela colocação de 3 discos em tubos de ensaio estéreis com 9 mL de meio de cultura Eagle e incubação a 37ºC por 24 h. O efeito citotóxico dos extratos foi avaliado utilizando o teste de incorporação de ³H-timidina. RESULTADOS: Os resultados indicaram que os componentes liberados pelas resinas foram citotóxicos para as células L929 exceto para as amostras tratadas em banho de água (p<0.05). Em comparação com o grupo sem tratamento, o banho de água diminuiu a citotoxicidade das resinas acrílicas. CONCLUSÃO: O tratamento em microondas não influenciou a citotoxicidade das resinas acrílicas para bases de próteses.